Optimalisasi Zakat, Wakaf dan Infaq untuk Mendukung Pembangunan Berkelanjutan - Aisyah, Siti; Marliyah, Marliyah (Universitas Pahlawan Tuanku Tambusai, 2025)
The optimization of zakat, waqf, and infaq is a crucial strategy in supporting sustainable development. This article explores the role of these Islamic financial instruments in addressing social, economic, and environmental challenges. By analyzing the potential for more organized and transparent management of zakat, waqf, and infaq, the article identifies how their contributions can enhance community welfare, reduce inequality, and support the Sustainable Development Goals (SDGs). The study also recommends policy strategies to strengthen collaboration between Islamic financial institutions, governments, and communities in maximizing the positive impact of these instruments.